The issues of government support for business: a case study of the Kazakhstan’s “Business Road Map 2020” Program - Urazgaliyev, Saken; Nurgaliyeva, Saule (Nazarbayev University Graduate School of Public Policy, 2017)
The international experience argues that small and medium enterprises (SMEs) play a critical role in economic development of the state. Over the years Kazakhstani policy-makers adopted various government support programs intended to assist, advise and facilitate SMEs’/entrepreneurs’ activity in the country. However, despite loads of government efforts to support vulnerable business entities in the country, Kazakhstani SMEs still face a lot of barriers and problems. The main objective of the research project is to explore the challenges of supporting SMEs/entrepreneurs in Kazakhstan within “Business Road Map 2020” State Program (BRM-2020 or Program) through examining to what extent the state support is accessible for Kazakhstani business entities and diagnosing the main problems that arise during the realization of the Program. This allows identifying the gaps and drawbacks in the Program implementation, which need to be addressed for improvement of the effectiveness in delivering the state support.
Keywords: government support; government support for business; Business Road Map 2020